„Ośrodek całej wystawy, jej mózg, stacja centralna kultury”. Książka na Powszechnej Wystawie Krajowej - Baszko, Agnieszka (Biblioteka Uniwersytecka w Poznaniu, 2018)
Na Powszechnej Wystawie Krajowej w Poznaniu (16 maja – 30 września 1929), będącej podsumowaniem dorobku dziesięciu lat istnienia niepodległej Polski w dziedzinie gospodarczej, społecznej i kulturalnej, nie zabrakło zagadnień związanych z szeroko pojętym tematem książki. Była ona obecna i widoczna w wielu pawilonach wystawowych (np. instytucji kulturalno-oświatowych, wychowania fizycznego, pracy kobiet, oświaty rolniczej i kultury wsi, w dziale bibliotek w Pałacu Rządowym), ale w dwóch miejscach eksponowano ją w sposób szczególny. W dziale Piękna Książka mieszczącym się w Pałacu Sztuki położono nacisk na zewnętrzną szatę książki i pokazano prace artystów grafików, wydawców, drukarzy i introligatorów. W pawilonie Prasa i Książka, zaprojektowanym przez Rogera Sławskiego, obok stoisk redakcji różnych tytułów prasowych umieszczono stoiska 20 wydawców książek z całej Polski (takich jak Gebethner i Wolff, M. Arct, Zakład Narodowy im. Ossolińskich, „Książnica-Atlas”, Drukarnia i Księgarnia Św. Wojciecha). Poznań przez kilka dni był ponadto stolicą polskiej książki – do miasta zjechali również miłośnicy książki i ludzie zawodowo z nią związani. W dniach 29 maja – 2 czerwca 1929 roku odbyły się II Zjazd Bibliotekarzy Polskich i IV Zjazd Bibliofilów Polskich, połączone z jubileuszem stulecia istnienia Biblioteki Raczyńskich i stulecia pierwszego wydawnictwa Biblioteki Kórnickiej.

The Polish General Exhibition, which was held in Poznań between May 16 and September 30, 1929) and summarized the economic, social and cultural achievements of independent Poland following the ten years of its existence, also included a number of manifestations that related to the broadly understood subject of books. This was particularly visible in a large number of exhibition sites (pavilions) (e.g. those of cultural and educational institutions, physical education centres, women’s and agricultural education institutions and in the library section of the Government Palace). However, two exhibition sites were particularly involved in the promotion of books. In the department of Beautiful Book, housed in the Palace of Arts, a particular attention was given to the presentation of the external appearance of the book and development of book design. The department featured works of a number of artists, art editors, publishers, printmakers and bookbinders. In the Press and Book pavilion, designed by Roger Sławski, next to the stalls presenting different editorial offices of newspapers and magazines, stalls of 20 publishers from all over Poland displayed their books (Gebethner i Wolff, M. Arct, Zakład Narodowy im. Ossolińskich, “Książnica-Atlas” and Drukarnia i Księgarnia Św. Wojciecha, among others). As a result, throughout a few days Poznań was a capital of Polish book when the city became a meeting point for book lovers and people professionally involved in book trade and publishing. Between May 29 and June 2, 1929, the 2nd. Convention of Polish Librarians and the 4th. Convention of Polish Book Lovers were held, accompanied by the centenary celebrations of the Raczyński Library and the first publishing house of the Kórnik Library.
“The core of the whole exhibition, its brain and central station of culture”. The book at the Polish General Exhibition
Keywords: Powszechna Wystawa Krajowa w Poznaniu (1929); książka; książka artystyczna; wydawcy; pawilon Prasa i Książka na PWK; II Zjazd Bibliotekarzy Polskich; IV Zjazd Bibliofilów Polskich; Polska 1918–1939; Polish General Exhibition in Poznań (1929); book; artistic books; publishers; Press and Book pavilion at the PGE; 2nd. Convention of Polish Librarians; 4th. Convention of Polish Book Lovers; Poland 1918–1939